Role of Financial Development in Economic Growth of Nepal: An Empirical Analysis - Gautam, Bishnu Prasad (NRB Economic Review, 2015)
Economic growth and financial development are closely related. The interaction between them is crucial and has attracted great attention of researchers. This study attempts to examine the relationship between economic growth and financial development in Nepal between 1975 and 2012. The paper has used Augmented Dickey-Fuller and Philips-Perron tests to test for the existence of unit root, Co-integration test to examine long run relationship and Granger Causality test to find out causal relationship. In addition, vector error correction method has been applied to find out the speed of adjustment and the dynamics of relationship. The empirical evidence confirms that the financial development causes economic growth. In fact, financial development is the cause for economic growth in terms of short-term dynamics, while economic growth sustains financial development in the long-run. Based on the empirical findings, this study recommends that it is necessary to launch the reform programs in the financial system to consolidate and improve the efficiency and effectiveness of the financial system as well as to cope with the emerging changes. Thus, it asks for the consolidation of the system not only for the positive reinforcement between economic growth and financial development but also for the post crisis resilience and sustainability.